Modulation of endogenous plasmalogens by genetic ablation of lysoplasmalogenase (Tmem86b) in mice - Sudip Paul; Pooranee Morgan; Gerard Pernes; Yvette Schooneveldt; Thy Duong; Natalie A. Mellett; Kevin Huynh; Andrew J. Murphy; Graeme I. Lancaster; Peter J. Meikle (Journal of Lipid Research)
Plasmalogens are a distinct subclass of glycerophospholipids that exhibit unique structural features, notably possessing a vinyl ether linkage at the sn1 position of the glycerol backbone. These specialized lipids play crucial roles in various biological functions. Although the biosynthetic pathway of plasmalogens has been well-characterized, their catabolism remains less studied. In this study, we investigated the impact of global and tissue-specific loss-of-function of a plasmalogen catabolizing enzyme, lysoplasmalogenase (TMEM86B), on circulatory and tissue lipidomes. We generated both global and hepatocyte-specific Tmem86b knockout mice using cre-loxP technology. Mice with homozygous global inactivation of Tmem86b (Tmem86b KO mice) were viable and did not display any marked phenotypic abnormalities. Tmem86b KO mice demonstrated significantly elevated levels of the plasmalogens, alkenylphosphatidylethanolamine (PE(P)), and alkenylphosphatidylcholine (PC(P)), as well as lysoplasmalogens, in the plasma, liver, and natural killer cells compared to their wild-type counterparts. The endogenous alkenyl chain composition of plasmalogens remained unaltered in Tmem86b KO mice. Consistent with the global knockout findings, hepatocyte-specific Tmem86b knockout mice also exhibited increased plasmalogen levels in the plasma and liver compared to their floxed control counterparts. Overall, our findings shed light on the role of Tmem86b in plasmalogen catabolism, demonstrating how its ablation leads to elevated plasmalogen levels in select tissues and cells. This study enhances our understanding of the regulatory mechanisms governing plasmalogen metabolism and highlights the potential of targeting Tmem86b to therapeutically raise plasmalogen levels.